Effectiveness of Blended Learning Modules as Correlates of Self-Efficacy of ALS Students: Basis for an Action Plan - Anduyan, Dennis B. (Future Science / FSH-PH Publications, 2021)
The study determined the effectiveness of blended learning modules as correlates to students' self-efficacy among students in the Alternative Learning Systems in Tagum, Davao del Norte during the second quarter of 2021. Findings will serve as bases for a proposed action plan. The researcher utilized quantitative, descriptive-correlational and predictive designs among 211 students in the Alternative Learning System in different centers in the Central Cluster in Tagum, Davao del Norte selected through random sampling. The researcher used adapted-and-modified questionnaires from the following: